Outlays and Programmes for the Hill Region of Assam for the Fourth Plan - Planning Commission (Planning Commission, Government of India, 1968)
This document presents the proposed outlays and development programmes for the hill districts of Assam under India’s Fourth Plan, as formulated by the Joint Centre–State Study Team following field visits conducted in 1966. The report identifies deep-rooted socio-economic, infrastructural, and administrative challenges faced by the hill regions and stresses the need for a district-specific and integrated planning approach. Recognizing the limitations of existing administrative arrangements, the proposals advocate the establishment of a dedicated planning authority to ensure coordinated and effective development. A total outlay of approximately ₹70.50 crores is proposed, with major allocations directed towards transport and communications, social services, agriculture, and community development. The document outlines sector-specific programmes focusing on road connectivity, agricultural modernization, irrigation, education, health, cooperatives, and small-scale industries, while emphasizing sustainable practices suited to the ecological conditions of hill areas. The proposals are exploratory and intended to evolve through continued consultation with state leadership and local institutions. Overall, the report provides a strategic framework aimed at accelerating balanced development, enhancing economic integration, and improving the living conditions of the hill populations of Assam.
Proposals of the Joint Centre-State Study Team, Planning Commission
Proposals of the Joint Centre-State Study Team, Planning Commission
Keywords: Fourth Plan; Hill Districts of Assam; Development Outlays; Regional Planning; Transport and Communications; Agricultural Development; Community Development; Social Services; Infrastructure Development; Cooperative Movement; Sustainable Development; Planning Authority